PENGARUH STRUKTUR MODAL, AKTIVITAS DAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reza Kurniawan Sitorus; Yansen Siahaan; Elly Susanti; Khairul Azwar (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
This research results can be concluded as follows, average LTDER and ROA tend to decrease while the average TATO and working capital tend to increase, the results of multiple linear regression testing revealed that the capital structure, activities and working capital have a positive effect on profitability, the correlation coefficient test results have a strong relationship between capital structure, activities, working capital with profitability. While the coefficient of determination (R Square) states that profitability is influenced by capital structure, activities and working capital dan the research hypothesis H0 is rejected, meaning that the capital structure, working capital, activities and significant effect on profitability. The suggestions for company in this research is that companies optimize debt management so that the debt that has been turned into corporate capital can be maximized, optimize inventory to increase sales, further improve the management of working capital so that capital can be used optimally to increase profits, the company more maximize asset management so that there is no accumulation of funds that will result in more optimal profit. Keywords: Capital Structure, Activities, Working Capital and Profitability